125 WARD-BASED MEDICAL TEAMS: IMPACT ON THE CARE OF THE OLDER PERSON WARD. (18th November 2021) - Whelan, A; Doyle, P; Ryan, C; Kaur, I; Mulroy, M
Abstract: Background: The COVID-19 pandemic forced healthcare management to make structural adaptations in the interest of infection control. One such adaptation is the introduction of ward-based medical teams. The multidisciplinary team (MDT) is one of the cornerstones of geriatric medicine. Therefore, we aimed to explore the perception of the care of the older person MDT on the introduction of ward-based medical teams. Methods: Qualitative data was collected on a geriatric ward in October 2020 via written questionnaire. The questionnaire analysed how the transition to ward based medical teams was perceived in terms of inter-professional collaboration and clinical service delivered to patients. Results: There were 14 respondents, 10 of whom were nursing staff (71%). 86% strongly agreed that the medical team was more accessible, with most interactions occurring face-to-face. Patient care and safety was thought to have improved, 79% and 71% of respondents respectively. 93% felt they had a better rapport with the medical team. 71% felt the MDT meeting is more effective, 57% believed the meeting had greater impact on patient care. However, 93% felt there was less workspace. 21% believed there were more daily admissions and 57% felt the majority of patient transfers from other wards were inappropriate. Overall 86% favoured ward-based medical teams, with 57% of staff reporting that the change led to increased personal job satisfaction. Conclusion: By increasing the geographic proximity of doctors to other professionals, doctors were more accessible, issues were tackled quicker, and there was less time wasted bleeping medical teams. Overall staff favoured a ward-based system. However, there are challenges implementing this system. Particular attention should be paid to the availability of adequate workspace, including telephones and computers. Ward transfers should be minimized as continuity of care can be compromised. Strategies should be implemented so medical charts are available to the MDT during consultant-led ward rounds.